An Investigation Into Syntactic And Semantic Features In The Conceptual Metaphors Expressing The Concept Of “Buddhism” In Trinh Cong Son’s Songs And Their English Translational Version - Lê Thị Cẩm Thảo (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
In light of Cognitive Linguistics, Metaphor is not only an important tool in human cognition and thought, but also plays a vital role in the conceptualization of abstract concepts like Buddhism. The concept is commonly viewed and expressed in terms of cognitive metaphors. This study attempts to conduct a cross-linguistic research into the conceptual metaphors expressing the concept of “Buddhism” in Trinh Cong Son’s songs and their English translational versions. Based on the theoretical background of cognitive metaphor and data collected from the questionnaire and interviews, this study attempts to explore cognitive metaphors denoting the concept of “Buddhism”. Besides, it also finds out and explains the similarities and differences in the cognitive metaphors used for this concept. This careful investigation might lay a foundation for some implication for teaching and learning English. It also helps Vietnamese learners of English achieve better communicative competence in a cross-cultural communication.